Bibliometric Analysis of Postgraduate Theses Employing Ultrasonographic Imaging in the Field of Dentistry in Türkiye - Ezgi Katı; Makbule Göktepe (Clinical Dentistry and Research, 2026)
Background and Aim: The aim of this study is to perform abibliometric analysis of master’s, doctoral, and dental specialtytheses conducted in the field of dentistry in Türkiye thatemployed ultrasonographic imaging.Material and Methods: A search was conducted using relevantkeywords on the website of the National Thesis Center of theCouncil of Higher Education. All master’s, doctoral, and dentalspecialty theses employing ultrasonographic imaging in the fieldof dentistry published up to December 31, 2025 were identified.The obtained data were listed in Microsoft Excel accordingto thesis type, publication date, university name and type,department in which the study was conducted, methodology,and keyword information. Descriptive statistics were used fordata analysis.Results: A total of 77 postgraduate theses meeting theinclusion criteria were identified. Thesis production increasedmarkedly after 2020, and the studies were largely concentratedin the departments of Oral and Maxillofacial Radiology. Mostof the studies had a clinical design, and the majority of theseswere supervised by senior academics. Keyword analysisindicated that theses primarily focused on temporomandibularjoint evaluation, masticatory muscles, and elastography-basedimaging techniques.Conclusion: The findings indicate that ultrasonographicimaging, particularly in oral and maxillofacial radiology, hasincreased over time in theses written at dentistry faculties inTürkiye. The predominance of clinical studies highlights thepractical applicability of ultrasonography, while the findingssuggest that it represents a promising modality with potentialfor broader integration into dental practice.